2018
DOI: 10.5719/hgeo.2018.121.6
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and risks: case of Bejaia city in Algeria

Abstract: Urbanization is a worldwide process, occurring rapidly with adverse consequences on the environment and people. More exactly, urbanization aggravates natural risks and creates additional articial risks; this is a key issue for urban planning, which can reduce the exposure and negative outcomes if its provisions are properly enforced. This article is based on observations from Bejaia, Algeria. Each year, the city suffers from disasters including oods, forest res and landslides. This situation has led to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…The literature review showed that coastal landscapes are subject to increasing demands and pressures; the present study explored the changes of landscapes in order to assess the anthropogenic pressure, especially that resulting from land use/land cover change, or urban sprawl, taking into account role played by the socioeconomic and political factors. In a nutshell, the results revealed that most changes are due to the "derogatory planning" [119,120], emphasizing the conflict between the local political factors, influenced by the local economy, and the national legislation. The study identified the specific driving forces (urbanization, including its mechanisms, and tourism), and provided additional evidence for the changes of coastline landscapes, which can be countered by policies for a sustainable landscape management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature review showed that coastal landscapes are subject to increasing demands and pressures; the present study explored the changes of landscapes in order to assess the anthropogenic pressure, especially that resulting from land use/land cover change, or urban sprawl, taking into account role played by the socioeconomic and political factors. In a nutshell, the results revealed that most changes are due to the "derogatory planning" [119,120], emphasizing the conflict between the local political factors, influenced by the local economy, and the national legislation. The study identified the specific driving forces (urbanization, including its mechanisms, and tourism), and provided additional evidence for the changes of coastline landscapes, which can be countered by policies for a sustainable landscape management.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is rarely the case, and development occurs only by exceptions, i.e., by developments that to not comply with the rules, but are exempted from these. This pattern is called derogatory planning [119,120]. For example, in Constanţa, the largest city of the Romanian seashore, the Master Plan was not updated for 18 years, but the real development was documented by over 3000 plans for different areas of the city, representing exceptions from the regulations imposed by the Master Plan [121].…”
Section: Land Cover/land Use Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…This has lead to economic growth, changes in spatial attributes and integration of urban activity systems and its relative dynamics are much higher than in the centres of the largest cities (Kowalczyka et al, 2019). Urbanization is a worldwide process which occurs rapidly, accompanied by adverse consequences on the environment and people (Hamma and Petrisor, 2018). Moreover, city planners and policy makers have an important role to play in tightening the village-to-city land conversion system and curbing expansions (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 60 years urbanization has occurred more forcefully than ever in the human history (Scott and Storper, 2015) and it has changed boundaries, morphologies and scales of human settlements (Vigano et al, 2017). Aggressive urbanization rendered the increase of artificial land (Petrișor, 2012;Lois González et al, 2016) by the contraction of agricultural land (Ianoş et al, 2010;Petrișor et al, 2010;Zitti et al, 2015;Hama and Petrișor, 2018), by deforestation (Ianoş et al, 2010;Zitti et al, 2015;Verma et al, 2017;Niţă et al, 2018), impacting water bodies and natural parks (Ianoş et al, 2010;Zitti et al, 2015), and generating complex process environmental conflicts (Ianoş et al, 2010;Petrişor et al, 2010;Ianoş et al, 2017).…”
Section: Introductionmentioning
confidence: 99%